Upaya Peningkatan Profesionalisme Guru Al-Islam dan Kemuhammadiyahan Pemula di Madrasah Ibtidaiyah Muhammadiyah - Indra Sukri; Aguswan Rasyid; Mursal (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2021)
This research was conducted in order to see problems such as some students during the learning process of teaching al-Islam material and Kemuhammadiyahan there are students who are noisy, chatty and so on, when the teacher of Al-Islam and Kemuhammadiyahan is finished. explaining and the teacher giving feedback or asking the students, some students do not understand and can not answer it, there are still many problems of student discipline in the subjects of Al-Islam and Kemuhammadiyahan when the teacher gives exercises or submits notes about Al-Islam and Kemuhammadiyahan, the majority of students are noisy and uneasy, those who are slow in learning Al-Islam and Kemuhammadiyahan do not respond to learning positively then are not motivated to learn. Related to the above problems, this study aims to outline the efforts made by leaders in improving teacher profession. The method used in this study is qualitative, data collection techniques include observation, interview and documentation studies. All data collected is then analyzed with a qualitative approach. The result of this study is that the efforts made by the leadership in improving the professionalism of al-Islam and Kemuhammadiyahan teachers are through coaching, routine activities of al-Islam and Islamic studies. There are several supporting factors that facilitate the realization of the improvement of the professionalism of al-Islam and Kemuhammadiyahan teachers in MI Teluk Kuantan is the full support of the leadership of Muhammadiyah Riau region.